Illocutionary Speech Act Used in Online Classroom Via Zoom Meeting by the Teacher and Students - Astita Maniwaty; Sri Fatta Meldawati; Sukmawati Sukmawati; Sri Wahyuni (Jurnal Dieksis ID, 2026)
The urgency of this research lies in the fact that Illocutionary Speech Acts used in online classrooms via Zoom meetings by teachers and students need to be understood to improve the effectiveness of virtual learning communication. This study examines illocutionary speech acts used by teachers and students in online classrooms conducted through Zoom meetings. The research is important because online learning during the Covid-19 pandemic changed classroom communication patterns and influenced how teachers and students interacted virtually. Understanding speech acts in online classrooms can help improve communication effectiveness in digital learning environments. This study applied a mixed-method approach combining quantitative and qualitative analysis. The population of the study consisted of utterances produced by teachers and students in an online classroom video uploaded on YouTube. The sample was selected purposively from a 57-minute online classroom interaction involving ninth-grade students. The research instrument was a transcription sheet based on the video subtitles. Data were collected through observation, watching the video repeatedly, transcribing the utterances, and classifying the data based on Searle’s taxonomy of illocutionary speech acts. The data were analyzed quantitatively by calculating the percentage of each speech act type and qualitatively by interpreting the functions of the utterances in the classroom context. The findings revealed that all five types of illocutionary speech acts were found in the online classroom interaction: assertive (50%), directive (34%), declarative (8%), expressive (6.9%), and commissive (1.1%). The study implies that assertive and directive speech acts play dominant roles in maintaining interaction and delivering information in online learning. In conclusion, online classroom communication through Zoom meetings involves various illocutionary speech acts, with assertive speech acts being the most frequently used by teachers and students.